Silage making economical and balanced feed for commercial dairy - Dhillon, Balwinder SINGH; Dhaliwal, A P S; Brar, Jitender Singh (Indian Farming, 2019)
The latest training, new techniques and research work help in making dairy farming occupationwork better. The present number of cattle in Punjab is about 81.2 lakh, which has 62.4 lakhlactating dairy animal. There is a need for substantial increase in the current yield of greenfodder to provide complete and good quality feed to animals. One animal gets 30.65 kg of fodderper day, which is very low. If 40 kg of green fodder is found in a large livestock daily, then thereis an annual requirement of 911 million tonnes of green fodder. The profitable dairy farming atthe farmer’s field can be achieved by reducing the input cost. The maximum expenditure (65-70%) among the inputs cost go to single item i.e. feeding cost. Among the different ingrediantsincluded in the feeding the cheapest source is green fodder. In our condition the production as wellas area under different fodder crops is not sufficient to meet out the green fodder requirements.The best way to cope up this deficiency we must increase area under fodder or preserve the greenfooder when the requirement in aboundant (as silage).